Pengaruh Model Komunikasi Guru Berbasis Realistic Approach Terhadap Peningkatkan Kreativitas Siswa SMA Negeri 6 Binjai - Rian Rama Putra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to determine the influence of teacher communication models based on realistic approaches on increasing student creativity at SMA Negeri 6 Binjai. The method used is a quantitative approach with a descriptive type of research. The research population consisted of students in class X (classes 105 and 107) with a sample of 64 respondents determined using the total sampling technique. The data collection technique was carried out through a questionnaire with a Likert scale. Data were analyzed using Pearson's Product Moment correlation test, significant test, simple linear regression, and determination test. The results of the study show that the teacher communication model based on a realistic approach has a positive and significant influence on increasing student creativity. This approach is able to encourage students to be more active, think critically, and produce diverse ideas and solutions in the learning process. Thus, the application of a realistic approach-based communication model is effective in increasing student creativity in the school environment.